2016
DOI: 10.21837/pm.v14i5.179
|View full text |Cite
|
Sign up to set email alerts
|

Main Criteria in the Development of Smart Cities Determined Using Analytical Method

Abstract: A smart city is one that is highly developed, innovative, environment-friendly, and incorporates relevant aspects of the economy, technology, mobility, quality of life and other aspects that contribute to the well-being of its residents. To achieve the status of a smart city, several requirements, criteria or indicators need to be considered. Strategic decisions by planners of a smart city play an important role in determining how the city uses resources and opportunities through the harnessing of modern techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Additionally, the city's ability to attract visitors, business, capital, and talent also increases its economic growth (Giffinger and Gudrun 2010). But, findings from the literature (Tahir and Malek 2016) suggested that economic development has frequently been linked with the depletion of resources, resulting in adverse consequences for future development. Hence, it is significant that smart cities manage natural resources (Washburn et al 2009).…”
Section: Smart Economymentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the city's ability to attract visitors, business, capital, and talent also increases its economic growth (Giffinger and Gudrun 2010). But, findings from the literature (Tahir and Malek 2016) suggested that economic development has frequently been linked with the depletion of resources, resulting in adverse consequences for future development. Hence, it is significant that smart cities manage natural resources (Washburn et al 2009).…”
Section: Smart Economymentioning
confidence: 99%
“…In smart cities, the environment dimension relates to the preservation of natural resources such as water, clean air, land, etc. (Tahir and Malek 2016). It involves the green utilization of natural resources, protection of natural habitat, reduced pollution, and sustainable management of resources (Giffinger et al 2007).…”
Section: Smart Environmentmentioning
confidence: 99%
See 3 more Smart Citations